Low plasma cortisol and fecal cortisol metabolite measures as indicators of compromised welfare in domestic horses (Equus caballus). - Jodi Pawluski; Patrick Jego; Séverine Henry; Anaelle Bruchet; Rupert Palme; Caroline Coste; Martine Hausberger (PLoS ONE)
The hypothalamic-pituitary-adrenal (HPA) axis response to chronic stress is far from straight forward, particularly with regards to animal welfare. There are reports of no effect as well as both decreases and increases in cortisol after chronic stressors. Therefore, the first aim of the present study was to determine how measures of compromised welfare, such as chronic pain and haematological anomalies, related to cortisol levels in domestic horses (Equus caballus). Domestic horses are an informative model to investigate the impact of chronic stress (due to environment, pain, work, housing conditions…) on the HPA axis. The second aim was to determine whether levels of fecal cortisol metabolites (FCM) may be used as an indicator of welfare measures. The present study used fifty-nine horses (44 geldings and 15 mares), from three riding centres in Brittany, France. The primary findings show that horses whose welfare was clearly compromised (as indicated by an unusual ears backward position, presence of vertebral problems or haematological anomalies, e.g. anaemia) also had lower levels of both FCM and plasma cortisol. This work extends our previous findings showing that withdrawn postures, indicators of depressive-like behavior in horses, are associated with lower plasma cortisol levels. We also found that evening plasma cortisol levels positively correlated with FCM levels in horses. Future research aims to determine the extent to which factors of influence on welfare, such as living conditions (e.g. single stalls versus group housing in pasture or paddocks), early life factors, and human interaction, act as mediators of cortisol levels in horses.